Parking Retribution At Leuwiliang Terminal Bogor Regency According To Law No. 28 Year 2009 - Andika, Dika Dwiputra; Hartini, Sri; Mustika, Desty Anggie (JURNAL MAHASISWA YUSTISI, 2023)
This research uses the Normative Juridical method, which concentrates research on secondary data sources (Library Research). In this research, data obtained from the literature and data obtained from the field after being collected are analyzed. In carrying out the supervision of the Bogor Regency Transportation Agency in increasing parking retribution according to Law Number. 28 of 2009 (Study at Leuwiliang Terminal, Bogor Regency). Assisted by the provisions of regional regulations that apply based on legislation and to realize the principle of regional autonomy, namely Bogor Regent Regulation Number 32 of 2021 concerning the Implementation of Motor Vehicle Parking. The obstacles of the Bogor Regency Transportation Agency include geographical factors, human resource factors, factors of holidays and national leave, factors of obedience of parking service users and supervision factors from the Bogor Regency Transportation Agency that are not optimal enough in supervising the parking at Leuwiliang Terminal, Bogor Regency, as a result many of the parking spots do not generate retribution. The efforts of the Bogor Regency Transportation Agency in increasing parking retribution at Leuwiliang Terminal, Bogor Regency, such as routine activities to conduct various evaluation monitoring on the performance of members of the Transportation Agency and also the parking area, collecting data and inventorying parking violations, supervising parking organizers and parking attendants and monitoring the parking area.